Gamma interferon-mediated increase in the number of Ia-bearing macrophages during infection with Listeria monocytogenes. - Koga, T (1987)
The role of gamma interferon (IFN-gamma) in an increase in Ia-bearing macrophages during Listeria monocytogenes infection was studied. The peritoneal macrophages from L. monocytogenes-infected mice contained a high proportion of Ia. Intraperitoneal injection of the supernatant from a culture of spleen cells from L. monocytogenes-infected mice induced Ia-rich exudates in normal mice. The Ia-inducing activity in the culture supernatant was abrogated by the pretreatment of spleen cells with anti-Thy-1.2 antibody plus complement. Immunoadsorption of the culture supernatant with anti-recombinant IFN-gamma antibody and protein A-Sepharose CL-4B completely abrogated its Ia-inducing activity. These results suggested that an increase in Ia-bearing macrophages during L. monocytogenes infection was attributable to T-cell-derived IFN-gamma.